OPG/RANK/RANKL signaling axis in patients with type I diabetes: Associations with parathormone and vitamin D - Paraskevi Karalazou; Dimitrios Ntelios; Fani Chatzopoulou; Aikaterini Fragou; Maria Taousani; Konstantina Mouzaki; Assimina Galli-Tsinopoulou; Sofia Kouidou; Georgios Tzimagiorgis (BMC, 2019)
Abstract Background Type 1 diabetes (T1D) has been associated with a higher fracture risk due to alterations in bone structure and metabolism. On the other hand, the important role of the RANKL/OPG/RANK signaling axis in bone physiology is well established. The aim of this study was to evaluate the levels of receptor activator of nuclear factor kappa-B ligand (RANKL), receptor activator of nuclear factor kappa-B (RANK) and plasma osteoprotegerin (OPG) levels, in T1D youngsters and to investigate factors that could influence the OPG/RANK/RANKL signaling axis such as 25-hydroxy vitamin D [25(OH) D], parathormone (PTH) and age. Methods Serum RANKL, RANK, 25(OH) D, PTH levels and plasma OPG levels, were measured in 71 youngsters with T1D and 50 healthy controls matched for age and gender. Results Plasma OPG levels were significantly lower (p = 0.025) in T1D patients compared to controls. Serum RANKL levels were significantly higher (p = 0.037), while no differences were observed in serum RANK levels (p = 0.946) between the two groups. Serum 25(OH) D levels found significantly decreased (p < 0.001) while serum PTH levels were significantly elevated (p < 0.001) in T1D patients than in controls. Conclusions Our results demonstrated that OPG and RANKL may be promising biomarkers for T1D patients. However, their circulating levels were associated with several factors including PTH, 25(OH) D and therefore, may represent an integrative biomarker for a variety of endocrine signaling disturbances observed in T1D.